2020
DOI: 10.3758/s13415-020-00789-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between early and recent life stress and emotional expression processing: A functional connectivity study

Abstract: The aim of this study was to characterize neural activation during the processing of negative facial expressions in a non-clinical group of individuals characterized by two factors: the levels of stress experienced in early life and in adulthood. Two models of stress consequences were investigated: the match/mismatch and cumulative stress models. The match/mismatch model assumes that early adversities may promote optimal coping with similar events in the future through fostering the development of coping strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 111 publications
(144 reference statements)
2
15
0
1
Order By: Relevance
“…The implementation of a task-based approach in our study allowed the detection of effects related to both the cumulative stress and match/mismatch models. The notion that both approaches are credible is in line with our previous study that showed the effect of both cumulative stress and an interaction between early and recent life stress on the processing of emotionally salient stimuli, namely emotional facial expressions (Sokołowski et al 2020). Moreover, the effects were independent of regulation goals.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The implementation of a task-based approach in our study allowed the detection of effects related to both the cumulative stress and match/mismatch models. The notion that both approaches are credible is in line with our previous study that showed the effect of both cumulative stress and an interaction between early and recent life stress on the processing of emotionally salient stimuli, namely emotional facial expressions (Sokołowski et al 2020). Moreover, the effects were independent of regulation goals.…”
Section: Discussionsupporting
confidence: 85%
“…However, the cumulative stress model explained the severity of psychopathological symptoms, while the match/mismatch model did not. In our previous study, both cumulative stress and the interaction between early and recent life stress were related to functional connectivity during the processing of facial emotional expressions (Sokołowski et al 2020), which suggests that the two stress models are not mutually exclusive. So far, no study has looked into these two models in the context of neural activation during cognitive reappraisal.…”
Section: Introductionmentioning
confidence: 85%
“…Based on our previous studies [ 48 ] and literature data [ 49 ], we hypothesize that the higher efficiency of spatial long-term memory combined with the higher the HPA axis reactivity, found in males with neonatal pain compared to females, may support the match/mismatch theory [ 50 ], which assumes the adaptive ability of moderate stress during the early critical period of development to prepare the organism to appropriate conditions of certain stressful environment (in our case, the formalin test) in adulthood. Indeed, the interaction of different types of stress (inflammatory pain-related stress in newborns, stress in the Morris water maze, and formalin-induced pain-related stress in the formalin test in adult rats) can lead to unexpected results [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, that the absence of differences in the reactivity of the HPA axis between Formalin and Control rats in our current study could be a consequence of the cumulative effects of testing in MWM and forced swimming on the activity of the HPA axis. The interaction of different types of stress, especially during critical periods of development, can lead to unexpected results ( Sokołowski et al, 2020 ). Especially interesting and of practical importance is the consequence of suppressing the adverse effects of one stress by another adverse stress ( Van Bodegom et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%